Pengaruh Marketing Public Relations Terhadap Loyalitas Distributor Kepada Merek SR12: Survey Pada Pedagang SR12 Di Kel. Rawabuntu Kec. Serpong - Dina Nurdiana; Lilik Sumarni (Institut Nalanda, 2024)
To achieve the highest level of brand loyalty, namely top of mind among loyal traders, SR12 producers carry out marketing public relations. This research aims to measure the influence of marketing public relations on SR12 brand loyalty among SR12 traders in kel. Rawabuntu subdistrict. Serpong. This research uses marketing public relations theory from Kottler & Keller, 2016, and brand loyalty from Aaker, 2014. This research methodology uses a quantitative approach with a survey method with a questionnaire instrument. The sample taken was 53 respondents who were SR12 traders in kel. Rawabuntu subdistrict. Serpong. The data analysis technique is simple linear regression. Overall, this research shows that the influence of marketing public relations on brand loyalty can be seen from the conclusion that the average value on variable X (marketing public relations) is 2.60 and the average value on variable Y (brand loyalty) is 3.00. It is shown that the calculated t coefficient value is 4.852 > t table 1.675 with a significance value of 0.000 which is still below 0.1, so the hypothesis in this study is accepted. And the hypothesis test was carried out using the t test based on the coefficient of determination R square value of 31.6% while the remaining 68.4% was influenced by other factors and the limitations of the error instrument. This explains that there is an influence of marketing public relations on SR12 brand loyalty among SR12 traders in kel. Rawabuntu subdistrict. Serpong..